2020
DOI: 10.1038/s41598-020-65329-x
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking climate warming effects on Alaskan soil microbial communities via gradual temperature increase

Abstract: Climate change can trigger shifts in community structure and may therefore pose a severe threat to soil microbial communities, especially in high northern latitudes such as the Arctic. Arctic soils are covered by snow and ice throughout most of the year. This insulation shields them from high temperature variability and low surface temperatures. If this protective layer thaws, these soils are predicted to warm up at 1.5x to 4x the rate of other terrestrial biomes. In this study, we sampled arctic soils from si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…At the RNA level, microbial community composition results showed that Chloroflexi and Gemmatimonadetes were more resistant to the extreme stratospheric environment than Cyanobacteria, especially Kallotenue and Longimicrobium (Figure 4). Chloroflexi is a dominant bacterial phylum in many extreme environments, such as alkaline hot springs, deep lakes, and arctic soils [59][60][61]. Chloroflexi can be photoautotrophic, chemoautotrophic, or mixotrophic, and they can adapt their metabolic strategy depending on the prevailing environmental conditions [62,63].…”
Section: Regulation Of Microbial Communities By Stratospheric Environ...mentioning
confidence: 99%
“…At the RNA level, microbial community composition results showed that Chloroflexi and Gemmatimonadetes were more resistant to the extreme stratospheric environment than Cyanobacteria, especially Kallotenue and Longimicrobium (Figure 4). Chloroflexi is a dominant bacterial phylum in many extreme environments, such as alkaline hot springs, deep lakes, and arctic soils [59][60][61]. Chloroflexi can be photoautotrophic, chemoautotrophic, or mixotrophic, and they can adapt their metabolic strategy depending on the prevailing environmental conditions [62,63].…”
Section: Regulation Of Microbial Communities By Stratospheric Environ...mentioning
confidence: 99%
“…Some long-term warming studies on microbial communities have shown alterations of both soil bacterial and fungal communities (Deslippe et al 2012). However, other studies have demonstrated a decrease in soil microbial growth or no significant changes (Lamb et al 2011;Rinnan, Michelsen, and Bååth 2011;Ballhausen et al 2020), with still others showing increased microbial nutrient mobilization only if competing plants are eliminated (Schmidt et al 2002). It is likely that both abiotic and biotic factors play a role in explaining these variable responses.…”
Section: Long-term Warming Plots As Simulations Of Climate Changementioning
confidence: 99%
“…It would be interesting to continue monitoring these warmed plots in the future because significant impact of warming on soil communities may require longer experimental treatment time than a dozen years, although it is noted that not all researchers support longer-term experiments (Ballhausen et al 2020). Alternatively, because temperatures in the greenhouses on rare extremely warm days can rise as much as 13°C above ambient (Zamin and Grogan 2012), combined with rising background climate change-associated increases, future warming experiments could provide unrealistic conditions for arctic soil communities and unduly stress the plants.…”
Section: Long-term Warming Plots As Simulations Of Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…The soil microbial community can be structured by warming via three main pathways: 1) direct abiotic effects of temperature, and indirect biotic interactions mediated by 2) plants and 3) higher level consumers. Microbial community structure may not be sensitive to a few degrees of Celsius warming in a short term (~ a few months) as demonstrated in lab incubations (11,12) but see (13). On the other hand, microbial communities may be structured by indirect effects mediated by plants which can instantly respond to warming (14).…”
mentioning
confidence: 99%